Bone Marrow Mesenchymal Stromal Cell-mediated Resistance in Multiple Myeloma Against NK Cells can be Overcome by Introduction of CD38-CAR or TRAIL-variant. Issue 5 (21st May 2021) - Holthof, Lisa C.; Stikvoort, Arwen; van der Horst, Hilma J.; Gelderloos, Anne T.; Poels, Renée; Li, Fengzhi; Groen, Richard W. J.; Zweegman, Sonja; van de Donk, Niels W. C. J.; O'Dwyer, Michael; Mutis, Tuna
Abstract : Supplemental Digital Content is available in the text. Abstract : We have recently shown the strong negative impact of multiple myeloma (MM)-bone marrow mesenchymal stromal cell (BMMSC) interactions to several immunotherapeutic strategies including conventional T cells, chimeric antigen receptor (CAR) T cells, and daratumumab-redirected NK cells. This BMMSC-mediated immune resistance via the upregulation of antiapoptotic proteins in MM cells was mainly observed for moderately cytotoxic modalities. Here, we set out to assess the hypothesis that this distinct mode of immune evasion can be overcome by improving the overall efficacy of immune effector cells. Using an in vitro model, we aimed to improve the cytotoxic potential of KHYG-1 NK cells toward MM cells by the introduction of a CD38-specific CAR and a DR5-specific, optimized TRAIL-variant. Similar to what have been observed for T cells and moderately lytic CAR T cells, the cytolytic efficacy of unmodified KHYG-1 cells as well as of conventional, DR5-agonistic antibodies were strongly reduced in the presence of BMMSCs. Consistent with our earlier findings, the BMMSCs protected MM cells against KHYG-1 and DR5-agonistic antibodies by inducing resistance mechanisms that were largely abrogated by the small molecule FL118, an inhibitor of multiple antiapoptotic proteins including Survivin, Mcl-1, and XIAP. Importantly, the BMMSC-mediated immune resistance was also significantly diminished by engineering KHYG-1 cells to express the CD38-CAR or the TRAIL-variant. These results emphasize the critical effects of microenvironment-mediated immune resistance on the efficacy of immunotherapy and underscores that this mode of immune escape can be tackled by inhibition of key antiapoptotic molecules or by increasing the overall efficacy of immune killer cells.